Penerapan Protokol Kesehatan COVID-19 di Era New Normal Pada Kampung Tangguh Desa Karangdoro, Terminal Jajag, dan RTH Maron Genteng, Kabupaten Banyuwangi - Sugeng Winarso; Prastyantoko Kukuh; Prasetya Dhanny; Yuliani Elia; Pratiwi Ogis; Aprilia Rizqi (Pascasarjana Universitas Jember, 2020)
Corona Virus or COVID-19 is a virus outbreak in the early 2020 attacking the society and was a terrifying experience for people around the world. Banyuwangi is a regency affected by Covid-19 with the data distribution including 1911 persons positively infected, 1463 persons recovered, and 159 mortality rates. Therefore, it is necessary to study the health protocol implementation in Banyuwangi to minimize the infections. The area of research includes Karangdoro village (resilient village), Jajag Bus station, and RTH Maron. Resilient village is supported by the head of the village to enable health protocol implementation to minimize Covid 19 and to empower its residence against the outbreak. Sanitation is not managed well in RTH Maron since water waste is not IPAL standardized. It indicates that health protocols in not well implemented in RTH Maron. Jajag Bus Station shows low awareness of people on health protocol implementation due to false information on COVID 19. Solution on health protocol in new normal era is obeying and implementing 3 steps including: Masque Wearing, distancing, and hand washing to improve body cleanliness to avoid viruses. Society at all level must be hand in hand to work together by strictly implementing Health Protocol. Keywords: New Normal, Covid19, Resilient Village Karangdoro, Terminal Jajag, RTH Maron.